Factors influencing nutrition literacy in patients of type 2 diabetes mellitus: a cross-sectional study - Zhang, Wenjuan; Zhang, Yibao; Sun, Ziyu; Wang, Jiaqi; Wu, Yuhong (Frontiers in Nutrition, 2025)
ObjectiveTo understand the current status of nutrition literacy in patients with type 2 diabetes mellitus and analyze its influencing factors, aiming to provide a basis for medical staff to construct nutrition management and education programs.MethodsA total of 790 patients with type 2 diabetes mellitus who met the inclusion exclusion criteria in Hangzhou City were selected from March 2024 to January 2025 using convenience sampling method. The researchers used a general demographic questionnaire and the Nutrition Literacy Scale for Patients with Type 2 Diabetes Mellitus.ResultsPatients with type 2 diabetes mellitus scored (100.56 ± 22.27) on the Nutrition Literacy Scale. The results of multiple linear regression analysis showed that place of residence, education level, glycosylated hemoglobin, diabetic complications, comorbidities, and duration of the disease were the main factors affecting their nutrition literacy (p < 0.05).ConclusionNutrition literacy of patients with type 2 diabetes mellitus is at upper middle range and is affected by a variety of factors. Healthcare professionals should construct a nutrition management and education program based on the influencing factors to help patients improve their nutrition literacy level and form healthy eating behaviors.